The egg production of hungarian speckled hen and speckled transylvanian naked neck hen - Benk, Ákos; Vidács, Lajos (Acta Agraria Debreceniensis, 2010)
Our Faculty has been dealing with the cross-breeding of Hungarian speckled hen to maintain the breed since 1977. We keep two breeds of the Hungarian speckled hen, the bare-neck variant and the feathered-neck type on the pilot farm. Because of the spread of intensive poultry keeping the population of these breeds has become endangered. Beside the gene preservation, we endeavour to find the best way for the production-purposeutilisation of the speckled hen stock. We examined the egg production of these breeds.